"I would not go to him": Focus groups exploring community responses to a public health campaign aimed at reducing unnecessary diagnostic imaging of low back pain. (18th February 2021) - Sharma, Sweekriti; Traeger, Adrian C.; Tcharkhedian, Elise; Harrison, Janet; Hersch, Jolyn K.; Pickles, Kristen; Harris, Ian A.; Maher, Chris G.
Abstract: Background: Community awareness of the harms of overdiagnosis remains low. Objective: To evaluate community responses to a public health campaign designed for health service waiting rooms that focuses on the harms of unnecessary diagnostic imaging for low back pain. Methods: We conducted two focus groups of 19 community members with or without low back pain in Sydney, Australia. This study formed the fourth and final stage of the development process of a public health campaign: (a) initial design, (b) expert review and revision, (c) online experiment and (d) community views & revision. We evaluated reactions to components of the campaign that included digital posters and an information leaflet using strong imagery and messaging about the risk of overdiagnosis. We conducted a qualitative thematic analysis to identify main themes. Results: Community members reacted with surprise, initial mistrust, and occasionally anger towards imagery and messaging that suggested diagnostic imaging tests could be unnecessary and harmful. With further reflection and discussion, and after reading longer format information about overdiagnosis, the participants found some of the messages informative and useful. Participants appeared to gain a better understanding of the concept of overdiagnosis and the importance of not rushing to imaging. Conclusions: Public health campaigns including posters and leaflets displayed in waiting rooms could raise awareness about overuse of diagnostic imaging and the harms of overdiagnosis more broadly. However, negative reactions are possible and must be managed carefully. Patient or Public Contribution: We involved a community participation manager who provided advice on the focus group discussion guide, participant recruitment and manuscript presentation.